Application of multitouch technology for educational purposes in primary school - Busiakiewicz, Mateusz; Romanowski, Andrzej (Wydawnictwo Politechniki Łódzkiej, 2015)
[...] This chapter presents application of multitouch educational game for introduction basic science terms and information for early elementary school students. The project is a multitouch educational game, aimed at the early elementary school children, titled ProjectWizard. Since children at the age are highly vulnerable to any stimuli, it is extremely important to lead them in the correct direction. It is not that important to convey them as much information as possible, but rather to excite the attention of children in science, pick their interest. The application could be used as an enhancement tool for learning at home, but also as a supplement to science classes, or during extra-curricular science activities. The effect in terms of qualitative feedback, its efficiency in enhancing learning, as well as the most important aspects of such applications are discussed here.[...]
Keywords: technologia multitouch - edukacja; szkoła podstawowa - nauczanie; gra edukacyjna; wielodotykowa gra edukacyjna; multitouch educational game; multitouch technology - education; primary school - teaching; educational game